Redescription of two European species of Acerentomidae (Protura) belonging to the Italian fauna - Galli, Loris; Capurro, Matteo; Costa, Fabio; Stadio, Gabriele Di; Sarà, Antonio; Zinni, Matteo (Zootaxa, 2016)
Acerentulus apuliacus Rusek & Stumpp, 1988 is redescribed based on new specimens collected in Apulia and Basilicata (S-Italy) and deposited in the collection of Geneva Natural History Museum. Podolinella ruseki (Nosek, 1967) new combination is redescribed, based on the holotype from Austria and additional specimens collected in Liguria, NW Italy. The new material is deposited in the collection of the Dipartimento di Scienze della Terra, dell’Ambiente e della Vita, University of Genoa.